SYSTEM ADMINISTRATION TOOLS ELECTRICITY SALES IN PT. ELECTRIC LIGHT FOR USING VISUAL BASIC 6.0 - Novi Gwi Ratna; Ristyawati Ristyawati, Skom, MMsi (Jurnal Sistem Informasi, 2005)
This final project proposed administrative system turnover at PT. Use the LightElectric. Sales administration system in PT. Electric Light in its activities in order tonot use a computerized system, but still use the book as a means of recording. Thisresulted in activities that do not require a short time and reduce the effectiveness ofperformance. Therefore, in overcoming the existing problems as well as an input inimproving the administrative system of the existing sales, the writer feels the need fora change in the administration system, namely by using the computer so that data canbe processed with good, fast, and accurate.